RELEVANCE OF THE PROBLEM OF QUALITY OF EDUCATION AND HUMAN CAPITAL IN HIGHER EDUCATION - Raxmonova Manzura Shokirovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it is considered that the relevance of the problem of education quality management is related to socio-cultural changes in the society and changes in the education policy of the state.